2006
DOI: 10.1530/rep.1.00958
|View full text |Cite
|
Sign up to set email alerts
|

The role of bone morphogenetic proteins 2, 4, 6 and 7 during ovarian follicular development in sheep: contrast to rat

Abstract: The intraovarian roles of BMP family members such as BMP2, 4, 6 and 7 are not well understood, particularly in species with low ovulation rates such as sheep. Therefore, the objectives of these experiments were to determine the expression patterns of mRNAs encoding BMP2, 4, 6 and 7 during ovarian follicular development in sheep, and to determine the effects of these growth factors on ovine granulosa cell functions in vitro. For comparative purposes, the effects of these BMPs were also determined in rat granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 41 publications
2
68
0
1
Order By: Relevance
“…In the ovary, investigations on BMPs are mainly studied in the follicle of rat (Erickson & Shimasaki, 2003), cow (Glister et al, 2010) and ewe (Juengel et al, 2006). Except a solitary report by Erickson & Shimasaki (2003) on rat, no study could be found on BMPs in the CL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ovary, investigations on BMPs are mainly studied in the follicle of rat (Erickson & Shimasaki, 2003), cow (Glister et al, 2010) and ewe (Juengel et al, 2006). Except a solitary report by Erickson & Shimasaki (2003) on rat, no study could be found on BMPs in the CL.…”
Section: Discussionmentioning
confidence: 99%
“…The mid CL showed a significantly increased expression of BMP6 transcripts ( Figure. 1), which is consistent with the results of western blot ( Figure. 2A and B) and immunofluorescence ( Figure. 3).Though BMP6 mRNA was highly expressed in the theca cells and the oocytes of rat (Erickson & Shimasaki, 2003) and cow (Glister et al, 2004), it was only expressed in oocytes in the follicle of ewe (Juengel et al, 2006). In bovine GCs, BMP6 upregulated basal and IGF stimulated Estrogen (E2) production (Glister et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The BMP-6 protein is expressed in oocytes (ovine: Juengel et al 2006, murine: Otsuka et al 2001bovine: Glister et al 2004;porcine: Brankin et al 2005a), granulosa (murine: Erickson & Shimasaki 2003;bovine: Glister et al 2004;porcine: Brankin et al 2005a), and theca cells (ovine: Campbell et al 2004;bovine: Glister et al 2004) of ovarian follicles during different stages of development. As part of its biological function, BMP-6 forms heteromeric complexes with a type I and type II receptor.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that BMP-6 controls steroidogenesis as well as granulosa and theca cell proliferation in ovine (Juengel et al 2006) and porcine (Brankin et al 2005a). Juengel et al (2006) established that BMP-6 inhibits ovine granulosa cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation